2017
DOI: 10.1186/s40001-017-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute reverse annular remodeling during MitraClip® therapy predicts improved clinical outcome in heart failure patients: a 3D echocardiography study

Abstract: BackgroundTranscatheter mitral valve repair (TMVR) has been shown to have acute effects on mitral valve geometry in patients with functional mitral regurgitation (FMR). This study investigates the impact of MitraClip® therapy-induced annular remodeling on clinical outcome and mitral regurgitation in heart failure patients.MethodsTMVR was performed successfully in 45 patients with FMR. In this study, mitral valve datasets were obtained before and directly after MitraClip® implantation using three-dimensional (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…As shown by others, assessment of global left ventricular longitudinal strain might better reflect LV systolic function in patients with MR after MV repair. Our findings are in line with previous studies, which reported absence or only minor changes of the LVEF despite significant improvement in the end‐diastolic pressure–volume relationship. This indicates that the beneficial effect of MC might less be reflected by improved LVEF, but rather due to the redirection of the regurgitation volume.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As shown by others, assessment of global left ventricular longitudinal strain might better reflect LV systolic function in patients with MR after MV repair. Our findings are in line with previous studies, which reported absence or only minor changes of the LVEF despite significant improvement in the end‐diastolic pressure–volume relationship. This indicates that the beneficial effect of MC might less be reflected by improved LVEF, but rather due to the redirection of the regurgitation volume.…”
Section: Discussionsupporting
confidence: 93%
“…LVRR after MC therapy occurred in 49% of the patients. Even though prior publications used the 6‐months period to assess for LVRR, we included in the final analysis only patients who completed both 6‐ and 12‐months follow‐up in order to evaluate whether the LVRR persisted during longer follow‐up. Indeed, a decrease in left ventricular dimensions became already evident after 6 months and further improved after 12 months, underlining the consistency of the study findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary limitation of this study is that our calculations were not optimized with experimental data obtained after MitraClip. On the other hand, SL annular dimension at end-diastole decreases between 2.8 to 4 mm in patients with FMR after MitraClip [3638] and Lurz et al found that the MRI-measured radial strain averaged across all sectors at the mitral valve level decreased from 15.4 to 9.6% after MitraClip in a cohort of mostly FMR patients. [39] These findings show that our simulations are in agreement with clinical results.…”
Section: Discussionmentioning
confidence: 99%